Soviet Anti-Catholic Church Activities (1953–1967) - Streikus, Arūnas (Genocidas ir rezistencija, 1997)
One of the most important components of the historical process resulting from the Soviet totalitarian regime in Lithuania was the relationship between the totalitarian government and religion, and in this case its institutional expression, the Catholic Church. The ideological basis of the Soviet totalitarian regime was its communist ideology, which treated religion negatively and had a profound impact not only on the social fabric but also on the life of every individual. Moreover, the Catholic Church in post–war Lithuania remained the only legal institution whose internal life was not completely controlled by the totalitarian regime, which allowed the idea of personal and national freedom to flourish. Thus, without a thorough assessment of these relations, it is impossible to have a good understanding of the Soviet period of Lithuanian history. Unfortunately, the situation of the Catholic Church in the Soviet totalitarian system has not yet received sufficient attention from Lithuanian scholars. More attention in historiography and scientific journalism was given only to the situation of the Church in the first post–war years and in the 1970s and 1980s. In the first case, this was due to the desire to reveal the Catholic Church’s links with the armed partisan resistance movement and the tragic nature of this period, while in the second case it was due to the better availability of sources and the Church’s prominent place in the dissenting alliance. However, the period 1953–1967 is important because it was then that the relationship between the totalitarian authorities and religion had revealed itself in its purest form since the Soviet government’s anti–Church policy could no longer be based on the Church’s links with the secular opposition underground.